Assessing Preservice Teachers’ Knowledge of Area (Sains Humanika, 2014)
This paper attempts to assess pre service teachers’ knowledge of area. In this study, the researchers employed survey research design to assess pre service teachers’ knowledge of area. A set of questionnaire was employed to collect the data. Convenient sampling technique was employed to select the participants of the study. Respondents of the study consisted of 46 pre service teachers (majored or minored in mathematics) who are attending Bachelor of Science with Education program at a public university in Peninsula Malaysia. This paper presents the analysis of the responses of the pre service teachers related to a particular mathematical task, namely notion of area. The finding suggests that 78.26% of the pre service teachers in this study had successfully selected all the shapes that have an area. They had the correct notion of area that 2-dimensional shapes (closed plane shapes) and 3-dimensional shapes. Different categories of incorrect notion of area were identified. Implications of the findings were also discussed.
Keywords: Pre service teachers; knowledge of area; survey research design; convenient sampling technique